Quasi-in situ immersion characterization of grain structures evolution revealing the corrosion resistance of Al-Zn-Mg alloys with various Sc additions - Li, Ming-gao; Sun, Mei-yu; Meng, Ling-han; Guo, Xiao-bin (Journal of Central South University, 2023)
Al-Zn-Mg alloys have been investigated for the effect of Sc additions on corrosion resistance. The addition of Sc to Al-Zn-Mg alloys can more effectively retard recrystallisation during heat treatment and improve mechanical properties. Sc-added alloys show significant discontinuity in grain boundary precipitation. In addition, the distribution spacing of η precipitates at the grain boundary is the largest in the alloy with Sc content of 0.29 wt.%. The exfoliation corrosion test and microstructural recrystallisation analysis show the inhibitory effect of Sc addition on recrystallisation and hence the improvement in corrosion resistance. In-situ immersion corrosion results indicated that the uncorroded texture in Al-Zn-Mg alloy with 0.29 wt.% Sc content first showed a rapid decrease and then a rapid increase. The addition of Sc to Al-Zn-Mg alloy plays an important role in improving the surface texture and increasing the corrosion resistance in the early stages of corrosion.